The Importance Of Character Building In Physics Teaching And Learning Strategies - Parinduri, Sri Handayani (Institut Agama Islam Negeri Padangsidimpuan, 2025)
This study aims to examine the benefits of integrating character building into physics teaching and learning strategies. It adopts a descriptive qualitative approach, using survey research methods through both a literature review and field observations. The literature review was carried out by consulting books and reputable online sources. The field study involved observing the significance of character building in the teaching and learning methods of fifth-semester physics students during the 2025/2026 academic year, with a group of four students. Key aspects of character building identified in the study included honesty, discipline, self-confidence, empathy, creativity, teamwork, and responsibility. The process of character development can be more effective when supported by moral education in various subjects, helping to nurture better character in students. One way this is reflected in physics lessons is by providing students with opportunities to apply character-building principles in their daily lives. The findings revealed that students experienced positive outcomes from the integration of character building into the physics teaching and learning strategies.